Holarctic phylogeographic structure of Eurasian wigeon (Mareca penelope) - I. V. Kulikova; Y. N. Zhuravlev; I. G. Korobitsyn; G. A. Nemkova; K. G. McCracken; J. L. Peters (Вавиловский журнал генетики и селекции)
The Eurasian wigeon (Mareca penelope) is one of the most numerous migrant species of waterfowl in the Palearctic. Annually, significant part of the world’s wigeon population makes seasonal flights over distances from tens to thousands or more kilometers. According to different estimates based on banding data, five geographic populations of the species were described in the Palearctic. However, distinct borders between the populations have not been identified. At the same time, no phylogeographic studies have been carried out for the complete native range of wigeon so far. In addition to the fundamental importance of such a study, knowledge of the genetic structure of populations is necessary for the development of measures to increase the number of and preserve this valuable game species. The aim of our work was a phylogeographic analysis of the wigeon across its vast native range in the Palearctic including ducks wintering in North America. We examined genetic diversity and differentiation of wigeon populations identified with banding data, phylogenetic relationships of mtDNA haplotypes and demographic history of populations and species as a whole by sequencing a 661 base-pair 5’-fragment of the mitochondrial control region from 195 individual ducks collected throughout the Palearctic and Nearctic. Genetic diversity was high in all studied populations. A reconstruction of haplotypes phylogeny revealed the absence of geographic structure in the data. Nonetheless, analysis of molecular variance (AMOVA) identified two groups of populations: EuropeanSiberian and East Asian. The former included wigeons from Europe, Siberia and the Atlantic coast of North America, and the latter comprised ducks from Russian Far East, Kamchatka Peninsula, Chukotka Autonomous District, the Aleutian Islands, Alaska, and the Pacific coast of North America.